New molecular variants of hypothalamus-pituitary-gonad axis genes and their association with early puberty phenotype in Bos taurus indicus (Nellore) - Milazzotto, M. P.; Rahal, Paula [UNESP]; Nichi, M.; Miranda-Neto, T.; Teixeira, L. A.; Ferraz, J. B. S.; Eler, J. P.; Campagnari, F. [UNESP]; Garcia, J. F. [UNESP] (Elsevier B.V., 2008)
Endocrine system plays a major role in the control of reproductive functions which are regulated by the hypothalamus-pituitary-gonad axis and its interactions. FSH and LH receptor genes are expressed at the gonads and GnRH receptor gene is expressed at the anterior pituitary gland. Misense mutations of the FSH, LH or GnRH receptors, activating or inactivating their functions in mammals, are potentially useful to allow the understanding of the role of this group of gonadotropins in reproductive phenotypes as early puberty and birth interval length. In the present study, polymorphisms in bovine exon 11 and 3'UTR of LHR, exon 10 and 3'UTR of FSHR and GnRHR genes were characterized with some of them resulting in changes in the aminoacidic chain. These polymorphic sites were found in a Bos taurus indicus (Nellore) female population by means of PCR-SSCP and DNA sequencing. Association between nucleotidic/aminoacidic changes and early puberty were determined by Chi-square analysis. It was found association between FSHR 3'UTR polymorphisms at position 2181, 2248 and 2249 bp and early puberty phenotype (p < 0.05). The presence of these new molecular markers might be considered in further studies to validate its correlation with early puberty or other reproduction associated phenotypes in cattle breeds. (C) 2007 Published by Elsevier B.V.
Keywords: LHR; FSHR; GnRHR; early puberty; Bovine; cattle